Baddest man : the making of Mike Tyson - Kriegel, Mark (Penguin Press, 2025)
"From the acclaimed New York Times bestselling author whose coverage of Mike Tyson and his inner circle dates back to the 1980s, a magnificent noir epic about fame, race, greed, criminality, trauma, and the creation of the most feared and mesmerizing fighter in boxing history. On an evening that defined the Greed is Good 1980s, Donald Trump hosted a raft of celebrities and high rollers in a carnival town on the Jersey Shore to bask in the glow created by a 21-year-old heavyweight champion. Mike Tyson knocked out Michael Spinks that night, and in 91 frenzied seconds earned more than the annual payrolls of the Los Angeles Lakers and Boston Celtics combined. It had been just eight years since Tyson, a feral child from a dystopian Brooklyn neighborhood was delivered to boxing's forgotten wizard, Cus D'Amato, living a self-imposed exile in upstate New York. Together, Cus and the Kid were an irresistible story of mutual redemption-darlings to the novelists, screenwriters and newspapermen long charmed by D'Amato, and perfect for the nascent industry of cable television. Long before anyone heard of Tony Soprano, Mike Tyson was HBO's leading man. It was the greatest sales job in the sport's history, and the most lucrative. But the business of Tyson concealed truths that were darker and more nuanced than the script would allow. The intervening decades have seen Tyson villainized, lionized, and fetishized-but never, until now, fully humanized. Mark Kriegel, an acclaimed biographer regarded as "the finest boxing writer in America," was a young cityside reporter at the New York Daily News when first swept up in the Tyson media hurricane, but here measures his subject not by whom he knocked out, but by what he survived. Though Tyson was billed as a modern-day Jack Dempsey, the truth was closer to Sonny Liston. Tyson was Black, feared, and born to die young. What made Liston a pariah, though, would make Tyson-in a way his own handlers could never understand-a touchstone for a generation raised on a soundtrack of hip hop and gunfire. What Peter Guralnick did for Elvis in Train to Memphis and James Kaplan for Sinatra in Frank, Kriegel does for Tyson. It's not just the mesmerizing ascent that he captures, but Tyson's place in the American psyche"-- Provided by publisher.